Performance of CT in the Preoperative Diagnosis of Cervical Lymph Node Metastasis in Patients with Papillary Thyroid Cancer: A Systematic Review and Meta-Analysis - Suh, C.H. (AJNR Am J Neuroradiol, 2017)
BACKGROUND AND PURPOSE: Ultrasound has become widely accepted as the first imaging technique used for the assessment of cervical lymph node metastasis in patients with papillary thyroid cancer. In this systematic review and meta-analysis, we evaluate the performance of CT for the preoperative diagnosis of cervical lymph node metastasis in patients with papillary thyroid cancer compared with ultrasound. MATERIALS AND METHODS: Ovid-MEDLINE and EMBASE data bases were searched for studies regarding the use of CT to diagnose cervical lymph node metastasis. The diagnostic performance of CT, ultrasound, and combined CT/ultrasound was assessed by using level-by-level and patient-based analyses. We also performed meta-analyses on the basis of the central and lateral neck levels. RESULTS: Nine eligible studies, including a total sample size of 1691 patients, were included. CT showed a summary sensitivity of 62% (95% CI, 52%–70%) and specificity of 87% (95% CI, 80%–92%) for diagnosing cervical lymph node metastasis when using level-by-level analysis. There was a positive correlation between the sensitivity and the false-positive rate (correlation coefficient, 0.807) because of the threshold effect. The summary sensitivity of combined CT/ultrasound (69%; 95% CI, 61%–77%) was significantly higher than ultrasound (51%; 95% CI, 42%–60%), though the summary specificity did not differ. CONCLUSIONS: The diagnostic performances of CT and ultrasound are similar, though CT and ultrasound combined are superior to ultrasound only. CT may be used as a complementary diagnostic method in addition to ultrasound for diagnosing cervical lymph node metastasis in patients with papillary thyroid cancer.